Towards Service Quality in Logistics in a Multi-Crisis Environment: The Combination of Lean and Digitalisation - Snarskė, Olga; Mockevičienė, Birutė (Vilnius University Proceedings, 2024)
Organisations operating in an environment of uncertainty are looking at 15-18 months to run operations at the same level as in the pre-crisis period. Therefore, companies have to focus on updating existing quality approaches, developing new models, and finding best practices. This paper aims to investigate the activities of a logistics company operating in Lithuania, which is implementing the lean philosophy through improving quality using information technology, and to analyse its actions in improving quality during the crisis. In order to achieve the set goal, the non-conformance management data of the parcel delivery company from 2016 to 2022 was analysed. During the research, it was found that the company had faced several crises, the most prominent of which was the increased demand for logistics services during the COVID-19 pandemic. The results show that new, emerging quality management challenges are managed by applying knowledge of lean management practices within two years.
Keywords: lean; digitalisation; logistics